Analysis of Supply Chain Performance of Banana Chips In Dahlia MSMEs - Haras, Abdul Fajar; Indriani, Ria; Bakari, Yuliana (Jambura Agribusiness Journal, 2023)
This study aims to analyze the performance of Banana chips supply chain management in Dahlia MSMEs, Gorontalo City in August-September 2022. This research method is a case study using primary and secondary data types. Data analysis techniques used in this study is the analysis of Supply Chain Operation Reference (SCOR) which then the calculation results will be compared with the data Benchmark. The results showed that of the 4 attributes with 7 assessment indicators only 4 indicators are in the superior category, namely perfect order fulfillment, delivery performance, cash to cash cycle and order fulfillment cycle while the other 3 indicators are volume flexibility, lead time and daily inventory are in the advantage category with the total cost used for Banana chips supply chain process is IDR. 7,560,000 in one production process. The impact for managerial is because the lead time that has not reached a superior position has a strong relationship with volume flexibility where long waiting times will result in the inability of the supply chain to maintain the flexibility of production volume, of course, this will have an impact on daily inventory, because it still have to wait for the schedule for the delivery of raw materials plus the production and marketing process.